Soy protein isolate: an overview on foaming properties and air–liquid interface. (25th October 2021) - Li, Jiaxin; Yang, Xiaoqing; Swallah, Mohammed Sharif; Fu, Hongling; Ji, Lei; Meng, Xiangze; Yu, Hansong; Lyu, Bo
Summary: Soy protein isolate (SPI) is widely used as a foaming agent due to its rich nutritional value and low price. Foaming is one of the key processing characteristics in food processing and is generally used in foam‐type foods. It plays an essential role in the flavour quality and appearance characteristics of food. Generally speaking, the foaming activity and foaming stability of regular SPI are not sufficient enough to meet the needs of practical applications. There is an urgent need to solve this drawback and improve the status quo of the food processing industry. The current research on the foaming properties of SPI across the globe focuses on improving foaming characteristics through optimising influencing factors and the use of different modification methods. Hence, this review aims to sort out the scientific research on the foaming mechanism of SPI and summarises evaluation methods, influencing factors and modification methods to improve the foamability of SPI to explore more applications of SPI. It will provide a theoretical basis for the production of SPI natural green active agents with good performance. Abstract : The foaming characteristics and properties of air‐liquid interface of soy protein isolates are affected by several factors, of which proper processing methods are suggested to aid improve the functional properties.